Entreguemos a emprêsa ao povo antes que o comunista a entregue ao Estado : os discursos da fração vanguardista da classe empresarial gaúcha na revista Democracia e Emprêsa do Instituto de Pesquisas Econômicas e Sociais do Rio Grande do Sul : (1962-1971) - Moraes, Thiago Aguiar de (2012)
This dissertation aims to analyse the discourse of the "vanguard" fraction of the businessmen from Rio Grande do Sul using the Democracia e Emprêsa journals published by the Instituto de Pesquisas Econômicas e Sociais do Rio Grande do Sul (IPESUL), from 1962 to 1971. The IPESUL was one of the regional segments of the central Institutos de Pesquisa e Estudos Sociais (IPÊS), located in Rio de Janeiro and in São Paulo. The numerous IPÊS, formed by civilians and military, launched a campaign to destabilize the João Goulart government in 1961 and contributed for his deposition. In 1964, several members of the IPÊS occupied high positions in the government. The discourses will be analyzed qualitatively and with the use of the concept of "ideology" as defined by John B. Thompson. We'll analyze how the articles in the journals were used, from 1962 to 1971, to stabilish or maintain relations of dominance between classes. In order to achieve our objective, this thesis was divided in three chapters, one on context and two with the analysis of the articles from the journals. In the first one, we'll deal with the foundation of the IPESUL, its founding partners and the campaign to destabilize the João Goulart government in Rio Grande do Sul, as well as with the institution's actions after the coup. We'll also work with the Democracia e Emprêsa journal, the editorial context in which it was published, the history of the journal per se and make some notes on the reception of the journal and the marketing strategies employed by its staff. In the second chapter, we'll analyze the point-of-view of the Rio Grande do Sul businessmen "vanguard" through essays on the idea of modernization of companies, on the defense of the "democracy", and on the opposition to "communism". In the third chapter, we'll work with the problems Brazil faced according to the social segment of the class we are analyzing and their suggestions on how to handle those issues.